TANGGUNG JAWAB HUKUM RUMAH SAKIT TERHADAP HAK PASIEN DI ERA PANDEMI COVID-19 - Hanna Wijaya; Muhammad Ali Hanafiah Selian (Yayasan Pendidikan Medika Indonesia, 2022)
According to the legislation, the hospital's legal responsibility to uphold the patient's rights cannot be divorced from its obligations to the patient. In actuality, the increasing number of Covid-19 instances in Indonesia has left hospitals unable to handle patients in need of therapy, particularly those with severe and critical diseases requiring intensive care units. With bed occupancy rates (BOR) in almost all hospitals above 85 percent, the community must recognize that hospitals must prioritize care for patients with moderate, severe, or life-threatening diseases. In any event, the Covid-19 epidemic had an effect on the quality of patient care received in hospitals. The study examined hospitals' legal obligation for preserving patient rights during the Covid-19 outbreak using normative juridical research methods and empirical evidence. The study's findings suggest that, despite constraints in providing great health care to patients, hospitals must protect patients' rights to safety and security while in the hospital. As a result, it is vital to construct a legal framework that protects the rights of health care employees and hospitals delivering services to patients during this pandemic, with a special emphasis on labor standards, occupational health and safety standards, and labor social security standards. The government must assist in terms of facilities and infrastructure by increasing the number of emergency hospitals to accommodate the anticipated increase in Covid-19 patients.